Chimera states in a neuronal network under the action of an electric field - Simo, Gaël R.; Njougouo, Thierry; Aristides, R. P. [UNESP]; Louodop, Patrick; Tchitnga, Robert; Cerdeira, Hilda A. [UNESP] (American Physical Society (APS), 2021)
The phenomenon of the chimera state symbolizes the coexistence of coherent and incoherent sections of a given population. This phenomenon identified in several physical and biological systems presents several variants, including the multichimera states and the traveling chimera state. Here, we numerically study the influence of a weak external electric field on the dynamics of a network of Hindmarsh-Rose (HR) neurons coupled locally by an electrical interaction and nonlocally by a chemical one. We first focus on the phenomena of traveling chimera states and multicluster oscillating breathers that appear in the electric field's absence. Then in the field's presence, we highlight the presence of a chimera state, a multichimera state, an alternating chimera state, and a multicluster traveling chimera.